The serve in under 12-13 Italian volleyball team - Parisi, F.; Raiola, G. (Journal of Human Sport & Exercise, 2014)
The serve is the technical skill with which a rally of a game of volleyball begins, and it can be performed by underhand, by a high float or drive and by a high jump. At the request of the coaches of national youth teams, the Italian Volleyball Federation (FIPAV) has adopted the mandatory underhand serve only for Under-12 and under 13 championships in order to favor the continuity of the game movement and passes of the ball over the net, which would be compromised in the event of a volleyball athlete who is particularly good at high jump serves. Although the abutment from the bottom appears to be more easily learned, not having the characteristics of offensiveness, must be abandoned as soon as it is able to perform the services more insidious. The increase in strength up to 11 years is very low and no difference between the sexes , he observes a slight increase up to 15 years, then intervenes when the phase of maximum development that leads to the peak at age 18. In this period there is also a progressive differentiation between females and males with a surge in favor of males estimated at a strength of about 40% greater than that of peers. The aim of this preliminary study was to see if an experimental study can be implemented, preceded by a pilot study in order to verify the hypothesis for the accuracy of the mandatory rule for the Under-12 and Under-13.